Observations and simulations of the interactions between clouds, radiation, and precipitation - Naegele, Alexandra Claire, author; Randall, David A., advisor; Kummerow, Christian D., committee member; Ramirez, Jorge A., committee member (Colorado State University. Libraries, 2016)
The first part of this study focuses on the radiative constraint on the hydrologic cycle as seen in observations. In the global energy budget, the atmospheric radiative cooling (ARC) is approximately balanced by latent heating, but on regional scales, the ARC and precipitation are inversely related. We use precipitation data from the Global Precipitation Climatology Project and radiative flux data from the Clouds and the Earth's Radiant Energy System (CERES) project to investigate the radiative constraint on the hydrologic cycle and how it changes in both space and time. We find that the effect of clouds is to decrease the ARC in the tropics, and to increase the ARC in middle and higher latitudes. We find that, spatially, precipitation and the ARC are negatively correlated in the tropics, and positively correlated in middle and higher latitudes. In terms of the global mean, the precipitation rate and the ARC are temporally out-of-phase during the Northern Hemisphere winter. In the second part of this study, we use a cloud-resolving model to gain a deeper understanding of the relationship between precipitation and the ARC. In particular, we explore how the relationship between precipitation and the ARC is affected by convective aggregation, in which the convective activity is confined to a small portion of the domain that is surrounded by a much larger region of dry, subsiding air. We investigate the responses of the ARC and precipitation rate to changes in the sea surface temperature (SST), domain size, and microphysics parameterization. Both fields increase with increasing SST and the use of 2-moment microphysics. The precipitation and ARC show evidence of convective aggregation, and in the domain average, both fields increase as a result. While running these sensitivity tests, we observed a pulsation in the convective precipitation rate, once aggregation had occurred. The period of the pulsation is on the order of ten simulated hours for a domain size of 768 km. The sensitivity tests mentioned above were used to investigate the mechanism of the pulsation. We also performed an additional test with no evaporation of falling rain, which leads to no cold pools in the boundary layer. Our results show that the period of the pulsation is noticeably sensitive to microphysics and domain size. The pulsation disappears completely when cold pools are prevented from forming, which suggests a "discharge-recharge" mechanism.
Keywords: clouds; model; radiation; convective aggregation; climate change; precipitation